Preparation method of flexible flame-retardant heat-insulating composite material and product
By modifying the polyurethane material, combining SiO2 aerogel and basalt fibers, a composite material with high thermal insulation and flame retardant properties was prepared, which solved the problem of flammable polyurethane material at high temperatures and improved basalt fibers The thermal insulation properties of fabrics realize the application of flame-retardant textiles.
Patent Information
- Application Number
- CN202411532880.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
AI Technical Summary
Existing polyurethane materials are flammable in high temperature environments and have poor flame retardant performance, which limits their application in certain fields. The thermal insulation performance of basalt fiber fabrics needs to be further improved to meet the needs in high temperature and complex environments.
By prepolymerizing materials such as isophorone diisocyanate, polycarbonate diol and gamma-aminopropyltriethoxysilane, SiO2 aerogel powder is added, and melting hot pressing technology is used to combine with basalt fiber fabrics. Flame-retardant and heat-insulating composite materials with high LOI values and internal pore structures were prepared.
The thermal insulation and mechanical properties of the material have been significantly improved, making it a flame-retardant textile, a Class A flame-retardant material, and the thermal insulation and safety performance have been greatly improved.
Smart Images

Figure CN119189379A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of textile (new material) technology, and specifically relates to a preparation method and product of a flexible flame-retardant and heat-insulating composite material. Background Art
[0002] With the increasing emphasis on fire safety and energy efficiency in modern society, the development of flame-retardant and thermal insulation materials is particularly important. Flame-retardant and thermal insulation materials can not only effectively prevent the spread of fire, but also protect equipment and personnel safety and reduce property losses when a fire occurs. In addition, in the fields of buildings, vehicles, and industrial equipment, good thermal insulation performance can reduce energy loss, improve energy efficiency, and promote energy conservation and emission reduction. Therefore, the research and development of efficient, environmentally friendly, and multifunctional flame-retardant and thermal insulation composite materials has important practical significance and broad market prospects.
[0003] Polyurethane (PU) materials are widely used in various fields due to their excellent mechanical properties and processing properties, but their flame retardant properties are poor and they are prone to combustion in high temperature environments, which limits their application in some special fields. For example, most polyurethane materials have softened their molecular chains at temperatures above 100°C and have thermally degraded at 220°C, seriously endangering life and property safety. In order to improve the flame retardant and heat resistant properties of polyurethane, modification research is needed. By adding flame retardants, changing the molecular structure or introducing new functional groups, the flame retardant properties and heat stability of polyurethane can be effectively improved, thereby broadening its application range.
[0004] Basalt fiber has great application potential in the field of thermal insulation materials. However, the thermal insulation performance of basalt fiber fabrics still needs to be further improved to meet the use requirements in high temperature and complex environments. Therefore, it is of great significance to study the thermal insulation modification of basalt fiber fabrics and improve their thermal insulation performance and high temperature resistance to promote the application of basalt fiber materials in the field of thermal insulation. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a flame retardant and heat-insulating composite material. The LOI value of the prepared flame retardant and heat-insulating composite material is greater than 40%, and it has an internal pore structure, which further improves the thermal insulation performance of the material and improves the mechanical properties, thereby achieving the purpose of making the composite material have flame retardant and heat-insulating functions.
[0006] As one aspect of the present invention, the present invention provides a method for preparing a polyurethane flame retardant heat insulating material, comprising the following steps:
[0007] (1) adding isophorone diisocyanate (IPDI), polycarbonate diol (PCDL1000), and 1-2 drops of dibutyltin dilaurate catalyst into a three-necked flask equipped with a mechanical stirring and condensation reflux device in an oil bath to carry out a prepolymerization reaction to obtain a polyurethane prepolymer PU;
[0008] (2) dissolving γ-aminopropyltriethoxysilane (KH550) in N,N-dimethylformamide (DMF), and slowly adding it dropwise to the polyurethane prepolymer using a constant pressure dropping funnel. After the addition is completed, a chain extension reaction is carried out in an oil bath to obtain silicon-modified polyurethane Si-PU;
[0009] (3) adding SiO2 aerogel powder to the solution obtained in step (2), and continuing to stir mechanically in an oil bath until uniform, to obtain a PU solution having flame retardant and heat insulating properties, which is recorded as Si-PU-SiO2;
[0010] (4) The PU solution with flame retardant and heat insulating properties obtained in step (3) is poured into a mold, placed in a vacuum drying oven, taken out after drying, and then the basalt fiber fabric and the modified polyurethane film are compounded by melt hot pressing technology to obtain a composite material with flame retardant and heat insulating properties, which is recorded as Si-PU-SiO2-BF.
[0011] The molar ratio of IPDI to PCDL1000 in step (1) is 2:1. The oil bath temperature is 60-80°C, and the prepolymerization time is 2h.
[0012] The molar ratio of KH550 in step (2) to IPDI in step (1) is 1:1, 20-40 mL of DMF is taken, the oil bath temperature is 60-80° C., and the chain extension reaction time is 2 h.
[0013] The mass ratio of SiO2 aerogel powder to solute in step (3) is 1:5 to 1:8. The oil bath heating temperature is 60 to 80°C; and the treatment time is 1 hour.
[0014] The melt hot pressing parameters in step (4) are: pressure 5 MPa, hot pressing time 10 min, and the thickness of the composite material is 1 to 2 mm.
[0015] The Si-PU-SiO2-BF flame retardant and heat-insulating composite material prepared by the present invention has a flame retardant performance test, and its LOI value is greater than 40%, which is a flame-retardant textile and a Class A flame retardant material; the thermal conductivity of PU is 0.5252W / mK, the thermal conductivity of Si-PU is 0.3945W / mK, and the thermal conductivity of Si-PU-SiO2 is 0.2729W / mK. Through the thermal insulation performance test, before modification, the temperature difference between the upper and lower surfaces of the PU material is 20°C, the temperature difference between the upper and lower surfaces of the basalt fiber fabric is 29°C, and the temperature difference between the upper and lower surfaces of the Si-PU-SiO2-BF flame retardant and heat-insulating composite material reaches 54°C, indicating that the thermal insulation effect is greatly improved.
[0016] The beneficial effects of the present invention are as follows: (1) The present invention improves the functionality of polyurethane materials by modifying them, and physically and chemically modifying them using KH550, basalt fiber and SiO2 aerogel, thereby giving them flame retardant and heat-insulating functions, slowing down the spread of flames, reducing flammability, and achieving the purpose of protecting safety;
[0017] (2) The thermal insulation performance of the materials before and after modification was tested using the thermal conductivity test method. The test results showed that according to the determination of the vertical damage length, smoldering and afterflaming time of textile combustion performance GB / T5455-2014, the afterflaming and smoldering time of the sample was ≤2, there was no melting or dripping phenomenon, and the fabric damage length was ≤100mm, which met the national standard requirements.
[0018] (3) The flame retardant performance of basalt fiber fabrics before and after modification was tested using the limiting oxygen index test method. The test results showed that the LOI value of the modified composite material was greater than 40%, which was a flame-retardant textile and a Class A flame retardant material. The thermal conductivity of PU was 0.5252W / mK, the thermal conductivity of Si-PU was 0.3945W / mK, and the thermal conductivity of Si-PU-SiO2 was 0.2729W / mK. Through the thermal insulation performance test, before modification, the temperature difference between the upper and lower surfaces of the PU material was 20°C, the temperature difference between the upper and lower surfaces of the basalt fiber fabric was 29°C, and the temperature difference between the upper and lower surfaces of the Si-PU-SiO2-BF flame retardant and thermal insulation composite material reached 54°C, indicating that the thermal insulation effect was greatly improved. At the same time, the mechanical properties were also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0020] Figure 1 This is the infrared image of PU before and after chemical modification in Example 1.
[0021] Figure 2These are SEM surface images of the PU film before and after SiO2 aerogel modification in Example 1, where (a) is before modification and (b) is after modification.
[0022] Figure 3 These are SEM cross-sectional screenshots of Si-PU-SiO2 after SiO2 aerogel modification in Example 1, where (a) is before modification and (b) is after modification.
[0023] Figure 4 This is the thermal conductivity diagram of the modified Si-PU-SiO2 composite film.
[0024] Figure 5 This is the design diagram of the Si-PU-SiO2-BF flame retardant and thermal insulation composite material in Example 1.
[0025] Figure 6 This is a scanning electron microscope image of commercially available basalt fiber fabric. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0027] Composite material thermal insulation performance test:
[0028] This test uses an ironing color fastness meter to compare the thermal insulation properties of the composite materials before and after modification. The ironing color fastness meter has an upper plate and a lower plate, and the two plates can be heated separately. The upper plate is fixed and heated to 80°C, and the lower plate is not heated. The composite material is clamped between the two plates and the test time is set to 10 minutes. When the set test time is reached, the ironing color fastness meter will emit a short beep and record the temperature of the lower plate at this time. The greater the temperature difference between the upper and lower plates, the better the thermal insulation performance of the tested material.
[0029] Fabric tensile strength and elongation at break test:
[0030] The mechanical strength performance of BF fabric, PU film, Si-PU-SiO2 film, PU@BF (PU filled with BF fiber), and Si-PU-SiO2-BF (BF fabric modified with Si-PU-SiO2) fabric samples were tested using a CMT4304 microcomputer-controlled electronic universal testing machine (MetS Industrial Systems Co., Ltd.). 25cm×5cm samples were cut respectively, with an effective measurement length of 20cm, and three parallel samples were set. The parameters were set, the machine was calibrated, the samples were fixed with a fixture, the instrument was started, and the measurements were taken in sequence.
[0031] Embodiment 1:
[0032] Step 1, preparation of polyurethane prepolymer:
[0033] 8.88 g of isophorone diisocyanate (IPDI) and 20 g of polycarbonate diol (PCDL1000) were mixed (molar ratio of 2:1), 1 drop of dibutyltin dilaurate catalyst was added, and then the mixture was added to an oil bath in a three-necked flask equipped with a mechanical stirrer and a condensation reflux device, and a prepolymerization reaction was carried out at 80°C in an oil bath for 2 hours to obtain a polyurethane prepolymer (denoted as PU).
[0034] Step 2, preparation of silicon-modified polyurethane:
[0035] 8.88 g of KH550 was dissolved in 20 mL of DMF and slowly added dropwise to the polyurethane prepolymer obtained in step 1 using a constant pressure dropping funnel. The molar ratio of KH550 to IPDI was 1:1. After the addition was completed, a chain extension reaction was carried out in an oil bath at 80° C. for 2 h to obtain a silane-modified polyurethane (denoted as Si-PU).
[0036] Step 3, preparation of polyurethane flame retardant heat insulation composite material:
[0037] 7g of SiO2 aerogel (hydrophobic, pore size 20nm, particle size 50μm, Shenzhen Zhongning Technology Co., Ltd.) powder was added to 37.8g of the silicon-modified polyurethane obtained in step 2, and mechanical stirring was continued in an 80°C oil bath for 1h to obtain a polyurethane material with thermal insulation properties, recorded as Si-PU-SiO2. At this time, the content of SiO2 aerogel was 15wt%. The obtained polyurethane material with thermal insulation properties was poured into a mold, placed in a vacuum drying oven, and taken out after drying to obtain a modified polyurethane film. After measurement, the thickness of the modified polyurethane film was 1.1mm. Then, the basalt fiber fabric (BF, plain weave, 200g / m 2 , Jiangsu Nongchaoer Composite Materials Co., Ltd.) and modified polyurethane film for compounding, basalt fiber fabrics were hot pressed on the upper and lower surfaces of the modified polyurethane film (see Figure 5 ), the melt hot pressing pressure is 5 MPa, the hot pressing time is 10 min, and the hot pressing temperature is 150°C, to obtain a composite material with flame retardant and heat insulating properties, recorded as Si-PU-SiO2-BF. After measurement, the thickness of the composite material is 1.9 mm.
[0038] Performance Test:
[0039] Table 1 Combustion performance of composite material Si-PU-SiO2-BF (Example 1)
[0040]
[0041]
[0042] Table 2 Thermal insulation properties of materials before and after modification (Example 1)
[0043]
[0044] Performance Analysis:
[0045] SEM analysis: Field emission scanning electron microscopy was used to observe the surface and cross-sectional morphology of the polyurethane material before and after modification. The results show that Figure 2 (a) and Figure 3 (a), the surface and cross section of the original polyurethane material are smooth, dense and without holes; Figure 2 (b) and Figure 3 (b) is a modified polyurethane material, which shows that the pore structure is evenly distributed on the surface and inside.
[0046] Combustion performance analysis: The combustion performance of the modified polyurethane composite material was analyzed. It was found that after the sample was modified by hot pressing, no melting or dripping occurred, the afterflaming time, smoldering time and degree of damage were reduced, and the LOI value increased, which still met the national standard requirements. The modified polyurethane composite material is a non-combustible fabric and fully meets the standard requirements for the outer fabric of fire retardant clothing.
[0047] Thermal insulation performance analysis:
[0048] As shown in Table 1, the ΔT of PU before modification is 20°C, the ΔT of Si-PU after silicon modification is 36°C, which is 80% higher than before modification, the ΔT of Si-PU-SiO2 is 49°C, which is 145% higher than before modification, and the ΔT of Si-PU-SiO2-BF is 54°C, which is 170% higher than before modification. The ΔT of PU@BF obtained by filling PU with BF is only 32°C, which is much lower than the effect of 54°C of coating modification of BF fabric.
[0049] Chemical structure analysis:
[0050] like Figure 1 As shown, the Si-PU spectrum has a peak at 2280 cm -1 3500cm -1 No obvious characteristic absorption peaks of -NCO and -OH groups were found, indicating that the polyurethane prepolymer and the modifier KH550 reacted completely. -1 The high-intensity absorption band at belongs to the characteristic Si-O-Si stretching vibration, which confirms the network structure connected by Si-O-Si bonds.
[0051] like Figure 6 As shown, although basalt fiber itself has good flame retardant and heat insulating properties, the basalt fiber fabric has gaps that allow hot air to penetrate, so the basalt fiber fabric cannot exert its heat insulating properties and cannot be used as a heat insulating fabric.
[0052] Table 3 Air permeability test of basalt fiber fabric (BF) and Si-PU-SiO2-BF
[0053]
[0054] It can be seen from Table 3 that the air permeability of Si-PU-SiO2-BF is significantly lower than that of basalt fiber fabric (BF).
[0055] Table 4 Tensile strength and elongation at break test (Example 1)
[0056]
[0057] Tensile strength performance analysis:
[0058] As can be seen from Table 4, the BF fabric is very easy to break, so the actual measured strength is only 427.1N. Although the tensile elongation at break of the PU film is high, its strength performance is very low. The tensile strength of PU@BF obtained by filling PU with BF is 28.3N. Although it is improved compared with PU, it is far lower than the strength performance effect of 1938.9N obtained by coating the BF fabric with a coating. Therefore, the mechanical properties of Si-PU-SiO2-BF are greatly improved after the BF fabric is coated with Si-PU-SiO2, which helps to better play the advantages of BF fabric and PU film.
[0059] Embodiment 2:
[0060] Step 1, preparation of polyurethane prepolymer:
[0061] 4.44 g of isophorone diisocyanate (IPDI) and 10 g of polycarbonate diol (PCDL1000) at a molar ratio of 2:1 and 1 to 2 drops of dibutyltin dilaurate catalyst were added to a three-necked flask equipped with a mechanical stirring and condensation reflux device in an oil bath, and a prepolymerization reaction was carried out at 80°C in an oil bath for 2 hours to obtain a polyurethane prepolymer (PU).
[0062] Step 2, preparation of silicon-modified polyurethane:
[0063] 4.44 g KH550 was dissolved in 20 mL DMF and slowly added to the polyurethane prepolymer using a constant pressure dropping funnel. The molar ratio of KH550 to IPDI was 1:1. After the addition was completed, a chain extension reaction was carried out in an oil bath at 80° C. for 2 h to obtain a silane-modified polyurethane (denoted as Si-PU).
[0064] Step 3, preparation of polyurethane flame retardant heat insulation composite material:
[0065] 2g of SiO2 aerogel powder was added to 18.88g of silicon-modified polyurethane obtained in step 2, and mechanical stirring was continued in an oil bath at 80°C for 1h to obtain a polyurethane material with heat insulation properties, which was recorded as Si-PU-SiO2. At this time, the content of SiO2 aerogel was 10Wt%. The obtained polyurethane material with heat insulation properties was poured into a mold, placed in a vacuum drying oven, and taken out after drying. After measurement, the thickness of the modified polyurethane film was 0.82mm. The basalt fiber fabric and the modified polyurethane film were then compounded by melt hot pressing technology to obtain a composite material with flame retardant and heat insulation properties. The basalt fiber fabric was hot pressed on the upper and lower surfaces of the modified polyurethane film, respectively. The melt hot pressing pressure was 5Mpa, the hot pressing time was 10min, and the hot pressing temperature was 150°C, which was recorded as Si-PU-SiO2-BF. After measurement, the thickness of the composite material was 1.6mm.
[0066] Performance Test:
[0067] Table 5 Combustion performance of composite material Si-PU-SiO2-BF (Example 2)
[0068]
[0069]
[0070] Table 6 Thermal insulation properties of materials before and after modification (Example 2)
[0071] Material <![CDATA[T1 / ℃]]> <![CDATA[T2 / ℃]]> Temperature difference ΔT / ℃ PU 80 60 20 BF 80 51 29 PU@BF 80 48 32 Si-PU 80 50 30 <![CDATA[Si-PU-SiO2]]> 80 38 43 <![CDATA[Si-PU-SiO2-BF]]> 80 34 50
[0072] Combustion performance analysis: The combustion performance of the modified polyurethane composite material was analyzed. It was found that after the sample was modified by hot pressing, no melting or dripping occurred, the afterflaming time, smoldering time and degree of damage were reduced, and the LOI value increased, which still met the national standard requirements. The modified polyurethane composite material is a non-combustible fabric and fully meets the standard requirements for the outer fabric of fire retardant clothing.
[0073] Thermal insulation performance analysis:
[0074] As shown in Table 5, the ΔT of PU before modification is 20°C, the ΔT of Si-PU after silicon modification is 30°C, which is 80% higher than the thermal insulation performance before modification, the ΔT of Si-PU-SiO2 is 43°C, and the ΔT of Si-PU-SiO2-BF is 50°C. The ΔT of PU@BF obtained by filling PU with BF is only 32°C, which is much lower than the effect of coating modification of BF fabric with coating, which is 50°C.
[0075] Table 7 Tensile strength and elongation at break test (Example 2)
[0076]
[0077]
[0078] Tensile strength performance analysis:
[0079] It can be seen from Table 7 that compared with Example 1, with the reduction of the amount of cross-linking agent KH550, the strength of the PU film decreased slightly from 0.95N to 0.78N, but the tensile elongation at break increased from 171.9% to 185.3%. Compared with Example 1, the strength of PU@BF obtained by filling PU with BF showed a similar trend, with the tensile strength decreasing from 28.3N to 27.2N and the elongation at break increasing from 52.4% to 73.5%. It can be seen that although the strength of the modified PU is improved compared with that of pure PU, it is far lower than the strength effect of 1868.5N obtained by coating the BF fabric with a coating. Therefore, the mechanical properties of Si-PU-SiO2-BF are greatly improved after the BF fabric is coated with Si-PU-SiO2, which helps to better play the advantages of BF fabric and PU film.
[0080] Comparative Example 1:
[0081] Step 1 and step 2 in the preparation process are the same as in Example 1.
[0082] Step 3, preparation of polyurethane flame retardant heat insulation composite material:
[0083] 7g of SiO2 aerogel (hydrophobic, pore size 20nm, particle size 50μm, Shenzhen Zhongning Technology Co., Ltd.) powder was added to 37.8g of silicon-modified polyurethane obtained in step 2, and mechanical stirring was continued in an oil bath at 80°C for 1h to obtain a polyurethane material with heat insulation performance, which was recorded as Si-PU-SiO2. At this time, the content of SiO2 aerogel was 15Wt%. Then, 5g of short fibers (single fiber length 0.5cm) of BF basalt fiber fabric of the same specifications as Example 1 were added to the Si-PU-SiO2 solution, and mechanical stirring was continued in an oil bath at 80°C for 1h to obtain a composite polyurethane material with internal filling modification of basalt short fibers, which was recorded as Si-PU-SiO2@BF. The composite solution was poured into a mold, placed in a vacuum drying oven, and taken out after drying to obtain a Si-PU-SiO2@BF film. After measurement, the thickness of the modified polyurethane film was 1.5mm.
[0084] Performance Test:
[0085] Table 8 Combustion performance (comparison between Example 1 and Comparative Example 1)
[0086]
[0087]
[0088] Table 9 Thermal insulation properties of materials before and after modification (comparison between Example 1 and Comparative Example 1)
[0089] <![CDATA[Si-PU-SiO2-BF]]> <![CDATA[Si-PU-SiO2@BF]]> Temperature difference ΔT / ℃ 54 45 Tensile strength / (N) 1938.9 186.5 Elongation at break / (%) 9.79 34.8
[0090] Performance comparison analysis: Compared with the BF fabric external coating modified composite material Si-PU-SiO2-BF, the BF short fiber internal filling modified composite material Si-PU-SiO2@BF has poor combustion performance, low thermal insulation performance, low tensile strength at break, and high elongation at break. The thermal insulation performance of Si-PU-SiO2@BF is lower than that of Si-PU-SiO2-BF because the BF external coating has a stronger heat barrier. The tensile strength at break of Si-PU-SiO2@BF is 186.5N, which is much lower than the breaking strength of Si-PU-SiO2-BF, which is 1938.9N. The elongation at break of Si-PU-SiO2@BF is 34.8%, which is higher than Si-PU-SiO2-BF, but is not conducive to the shape stability of the material. Therefore, the comprehensive performance of Si-PU-SiO2-BF is far better than that of Si-PU-SiO2@BF.
[0091] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a flexible flame retardant and heat insulating composite material, characterized in that: The following steps are included: Step 1) mixing isophorone diisocyanate, polycarbonate diol, and dibutyltin dilaurate catalyst to perform a prepolymerization reaction to obtain a polyurethane prepolymer PU; Step 2) dissolving γ-aminopropyltriethoxysilane in N,N-dimethylformamide, and slowly adding the solution to the polyurethane prepolymer obtained in step 1), and after the addition is completed, performing a chain extension reaction in an oil bath to obtain silicon-modified polyurethane Si-PU; Step 3) adding SiO2 aerogel powder to the silicon-modified polyurethane Si-PU obtained in step 2) and reacting in an oil bath to obtain polyurethane material Si-PU-SiO2 with heat insulation performance. Step 4) The polyurethane material Si-PU-SiO2 obtained in step 3) is poured into a mold and dried to form a modified polyurethane film. The basalt fiber fabric is hot-pressed on the upper and lower surfaces of the modified polyurethane film by melt hot pressing to obtain a flexible flame retardant and heat insulating composite material.
2. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1, characterized in that: In step 1), the molar ratio of isophorone diisocyanate to polycarbonate diol is 2:1, the prepolymerization temperature is 60-80° C., and the prepolymerization time is 2-3 hours.
3. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 1), the average molecular weight of the polycarbonate diol is 1000.
4. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 2), the molar ratio of γ-aminopropyltriethoxysilane to isophorone diisocyanate is 1:
1.
5. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 2), the chain extension reaction is carried out in the oil bath at a temperature of 60 to 80° C. and a chain extension reaction time of 2 to 3 hours.
6. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 3), the mass ratio of SiO2 aerogel powder to silicon-modified polyurethane Si-PU is 1:5 to 1:
8.
7. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 3), the oil bath reaction temperature is 60-80° C. and the reaction time is 1-1.5 h.
8. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: In step 4), the melt hot pressing pressure is 5 MPa, the hot pressing time is 10 min, and the hot pressing temperature is 150°C.
9. The method for preparing the flexible flame retardant and heat insulating composite material according to claim 1 or 2, characterized in that: The thickness of the flexible flame retardant heat insulation composite material is 1 to 2 mm.
10. The flexible flame retardant heat insulating composite material prepared by the method for preparing the flexible flame retardant heat insulating composite material according to claim 1.
Citation Information
Cited By
Flame-retardant heat-insulating basalt fiber fabric and preparation method thereof
CN122257242A